Daptomycin : a review of properties, clinical use, drug delivery and resistance - Vilhena, Cláudia Sofia Jorge (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014